Facilitating component separation and cascade resource utilization of sewer sludge using alkaline plant ash - Jiangbo Ding; Lei An; Yunfeng Liu; Hongjun Cui; Jun Wang; Rui Ma; Jinsuo Lu; Heliang Pang (Water Research, 2026)

A novel two-layered hydroxyapatite-strengthened anammox-partial denitrification/anammox reactor for advanced nitrogen removal : Performance and mechanisms - Shenghao Ji; Hongjun Zhao; Shen Cui; Yujie Chen; Haojie Qin; Kengo Kubota; Jianyong Liu; Yu-You Li (Water Research, 2026)

When and where do university-related travelers use ride-hailing? Evidence from 75 universities in Tianjin, China - Xinwei Ma; Jichi Zhao; Weijie Yu; Hongjun Cui; Yang Liu (Journal of Transport Geography, 2026)

Mass-flow control enhances nitrogen removal in a three-stage partial nitritation, anammox and partial denitrification/anammox system treating food waste digestate: Performance and N2O release characteristics - Shenghao Ji; Shen Cui; Hongjun Zhao; Haojie Qin; Tianyi Zhang; Yu Qin; Jianyong Liu; Yu-You Li (Environmental Research, 2026)

Generation and characterization of the monoclonal antibody against the heavy chain of American eel (Anguilla rostrata) IgM - Xiaolong Meng; Shuangshuang Cao; Hongjun Xie; Wenting Jiang; Rui Guo; Yuchen Zhuo; Qicheng Wang; Xinhua Chen; Zhengwei Cui (Fish & Shellfish Immunology, 2026)

Impact of the green economic efficiency on industry-urban integration in the Yangtze River delta region - Mingtao Zhao; Xingpeng Liu; Hongjun Yuan; Lianbiao Cui; Xuebao Fu (Environment, Development and Sustainability, 2026)

Defect-triggered S-scheme heterojunction coupled with single-molecular catalytic centers towards selective photocatalytic CO2 reduction to CO - Keyu Cui; Yujia Wang; Xingjing Zhang; Jiaming Li; Chunbo Liu; Liqiu Zhang; Hongjun Dong; Chunmei Li (Chemical Engineering Journal, 2026)

Performance enhancement evaluation of coal gangue aggregates based on chemical solution modification: mechanical properties and microstructural characteristics - Meng Gao; Hongjun Jing; Jun Dai; Shaojie Chen; Chaowei Zhang; Junwei Shan; Hengfei Zhang; Yuanquan Cui; Shixuan Lei (Chemical Engineering Journal, 2026)

Chemical and microbial mechanism governing simultaneous nitrogen and phosphorus removal by anammox-hydroxyapatite granules - Shen Cui; Shenghao Ji; Hongjun Zhao; Tianyi Zhang; Yu-You Li (Chemical Engineering Journal, 2025)

Unveiling gender disparities in metro usage using gender-inclusive smart card data: Evidence from Nanjing, China - Xinwei Ma; Sijin Kou; Yanjie Ji; Minqing Zhu; Hongjun Cui (Journal of Transport Geography, 2025)

Optimization of up-flow velocity enhances the performance of partial denitrification/anammox process in expanded granular sludge bed reactor based on the formation of hydroxyapatite - Shenghao Ji; Shen Cui; Hongjun Zhao; Haojie Qin; Yu Qin; Yujie Chen; Yu-You Li (Chemical Engineering Journal, 2025)

Controls of paleosedimentary environments and anthropogenic activities on coastal groundwater salinization: A case study of Laizhou Bay, China - Zhen Cui; Guangquan Chen; Xin Shan; Haitao Zhang; Qingjie Zhou; Tengfei Fu; Hongjun Yu; Xingyong Xu; Shenliang Chen (Marine Geology, 2025)

Electric vehicle range prediction considering real-time driving factors and battery capacity index - Xinwei Ma; Jiaao Li; Hongjun Cui; Long Cheng; Yanjie Ji; Jianbiao Wang (Transportation Research Part D: Transport and Environment, 2025)

Multi-state road network modeling and vulnerability assessment in regional areas for earthquake rescue - Hongjun Cui; Yue Su; Xiushi Dong; Minqing Zhu (Natural Hazards, 2025)

The role of SYK phosphorylation in LPS-induced immunoglobulin responses of B cells in large yellow croaker (Larimichthys crocea) - Hongjun Xie; Shuangshuang Cao; Yueming Chen; Zhiqiang Wang; Xinhua Chen; Zhengwei Cui (Fish & Shellfish Immunology, 2025)

Molecular characterization of large yellow croaker (Larimichthys crocea) coagulation factor Ⅶ-like and its function on macrophage proliferation and polarization - Yueming Chen; Han Zhao; Shuangshuang Cao; Hongjun Xie; Jieyu Huang; Xinhua Chen; Zhengwei Cui (Fish & Shellfish Immunology, 2025)

Corrigendum to “Changing conventional blending photocatalytic membranes (BPMs): Focuson improving photocatalytic performance of Fe3O4/g-C3N4/PVDF membranes through magnetically induced freezing casting method” [Chem. Eng. J. 365 (2019) 405–414] - Binrong Li; Minjia Meng; Yanhua Cui; Yilin Wu; Yunlei Zhang; Hongjun Dong; Zhi Zhu; Yonghai Feng; Chundu Wu (Chemical Engineering Journal, 2024)

What influences intermodal Choices: Metro-Centric, Bus-Centric, Hybrid? insights from Machine learning Approaches - Xinwei Ma; Xiaolin Tian; Hongjun Cui; Mingjia He; Jianbiao Wang; Long Cheng (Transportation Research Part D: Transport and Environment, 2024)

Response of soil gross nitrogen mineralization to fertilization practices in China's uplands - Jun Wang; Yinghua Duan; Guanmo Li; Lu Zhang; Dejin Li; Kailou Liu; Xi'an Cui; Boku Zhou; Hongjun Gao; Xiaori Han; Junyong Ma; Shutang Liu; et al. (Journal of Cleaner Production, 2024)

TC activity affected the northern sea of the Shandong Peninsula over the past 1500 years and its driving mechanism - Wenzhe Lyu; Tengfei Fu; Zhen Cui; Yancheng Wang; Wenquan Liu; Xingyong Xu; Hongjun Yu (Marine Geology, 2024)

Quantitative trait locus analysis of gray leaf spot resistance in the maize IBM Syn10 DH population - Lina Cui; Mingfei Sun; Lin Zhang; Hongjie Zhu; Qianqian Kong; Ling Dong; Xianjun Liu; Xing Zeng; Yanjie Sun; Haiyan Zhang; Luyao Duan; Wenyi Li; et al. (Theoretical and Applied Genetics, 2024)

How temporary disruption of metro service influence metro commuters’ mode shifts during the COVID-19 pandemic? Evidence from Tianjin, China - Xinwei Ma; Shaofan Sun; Lin Li; Mingjia He; Hongjun Cui (Travel Behaviour and Society, 2024)

Sedimentary evolution of the East China Sea with implications for the relationship between the East Asian winter and summer monsoon over the past 6.3 ka - Wenzhe Lyu; Tengfei Fu; Guangquan Chen; Qiao Su; Wenquan Liu; Yancheng Wang; Zhen Cui; Hongjun Yu; Xingyong Xu (Journal of Asian Earth Sciences, 2024)

Evaluation and determinants of metro users' regularity: Insights from transit one-card data - Xinwei Ma; Xiaolin Tian; Zejin Jin; Hongjun Cui; Yanjie Ji; Long Cheng (Journal of Transport Geography, 2024)

Taxonomic and functional dynamics of nirS denitrifiers along a salinity gradient in the Pearl River Estuary - Hongwei Zhou; Hao Zhang; Xinping He; Cheng Liu; Fozia; Qian Cui; Hongjun Yang; Chunyu Zhao; Han Zhang; Huanhuan Hu; Zongxiao Zhang (Frontiers in Marine Science, 2024)
Understanding the factors that shape the diversity, distribution, and function of denitrifying microbes is vital for managing nitrogen cycling in these ecosystems. This study explores the diversity, biogeographic distribution, assembly processes, interaction, and denitrification potential of the nirS -encoding microbial community ( nirS denitrifier) in the Pearl River Estuary based on high-throughput and metagenomics sequencing dataset. The results of this study show that salinity is a crucial regulatory environmental factor that determines the spatial distribution, phylogenetic turnover, and co-occurrence patterns of nirS denitrifiers. Additionally, the dissolved organic carbon (DOC), suspended sediment concentration (SSC), and dissolved oxygen (DO) in water also significantly impact the biodiversity and abundance of nirS denitrifiers. Furthermore, our findings demonstrate that, in comparison to environmental factors, the ecological and evolutionary characteristics of nirS denitrifiers play a more prominent role in regulating their denitrification potential, suggesting that alterations in the microbial community within dynamic changes in estuarine water can profoundly affect its denitrification function. Our results indicate the significant roles of denitrification microbial structure and phylogenetic characteristics in maintaining their ecological functions. Future studies should continue to explore the interactions between microbial communities and environmental factors to further elucidate the denitrification process in estuaries and its implications for ecosystem health and water quality.

Groundwater salinization under the influence of paleo sea-level fluctuation: a case study in southern Laizhou Bay, China - Zhen Cui; Guangquan Chen; Shenliang Chen; Hongjun Yu; Keke Chen; Baichuan Ran; Tengfei Fu; Wenzhe Lyu; Yancheng Wang; Xueyan Jiang; Xihuang Zhong (Frontiers in Marine Science, 2024)
The groundwater environment in low-lying coastal regions is significantly impacted by global sea-level fluctuation. In Laizhou Bay, three large-scale transgressions have occurred since the late Pleistocene, resulting in the transformation of ancient seawater into brine. This brine has become a major contributor to groundwater salinity in the area. This study establishes a correlation between groundwater occurrence and paleoclimate changes in Laizhou Bay using borehole sediment data. The source and mechanism of groundwater salinity are analyzed based on sediment pore water characteristics and hydrogen and oxygen isotopes. The study reveals that the stratigraphic structures in the area consist of four layers: a Holocene transgressive layer, a continental confining bed from the late Pleistocene, a Cangzhou transgressive layer from the late Pleistocene, and a fluvial aquifer from the middle Pleistocene. All aquifers in the study area have been infiltrated by modern seawater, with the uppermost Holocene aquifer influenced by evaporation and leaching processes, the central late Pleistocene aquifer remaining relatively stable, and the lower middle Pleistocene aquifer affected by subsurface low salinity runoff and exhibiting an increasing trend with depth. Given the presence of numerous hydrogeological environments globally that are similar to the study area, the obtained mechanisms of groundwater salinization in this study will provide theoretical support for groundwater management in similar regions worldwide.

Assembly mechanisms of microbial communities in plastisphere related to species taxonomic types and habitat niches - Yi Sun; Hongjun Li; Jinyong Zhang; Haining Wang; Xiaoyu Cui; Xin Gao; Wenwen Qiao; Yuyi Yang (Marine Pollution Bulletin, 2024)

Effects of triclosan exposure on stem cells from human exfoliated deciduous teeth (SHED) fate - Shiwen Deng; Caifeng Li; Junqi Chen; Zhao Cui; Tong Lei; Hongjun Yang; Peng Chen (Science of The Total Environment, 2023)

Benthic bacterial communities indicate anthropogenic activity footprints in coastal area under long-term marine spatial planning practice - Yi Sun; Hongjun Li; Daixi Liu; Xiaocheng Wang; Quanming Wang; Xiaoyu Cui; Jingfeng Fan (Acta Oceanologica Sinica, 2023)

Simulation of transport mechanism of radium isotopes in aquifer on the southern coast of Laizhou Bay - Yancheng Wang; Guangquan Chen; Hongjun Yu; Xingyong Xu; Yinqiao Zou; Wenqing Zhao; Weitao Han; Wenzhe Lyu; Zhen Cui; Runtian Ding (Acta Oceanologica Sinica, 2023)

The Complete Genome Sequence of a Gossypol-Degrading Bacterial Strain, Raoultella sp. YL01 - Si Chen; Weishu Zhang; Huiling Zhang; Ying Cui; Feng Wang; Jing Wu; Hongjun Chao; Dazhong Yan (Current Microbiology, 2023)

Mitigating soil salinity stress with titanium gypsum and biochar composite materials: Improvement effects and mechanism - Xin Xu; Jiahui Wang; Yiming Tang; Xuedan Cui; Daibing Hou; Hongjun Jia; Shaobo Wang; Lin Guo; Jinhang Wang; Aijun Lin (Chemosphere, 2023)

Sufentanil combined with parecoxib sodium inhibits proliferation and metastasis of HER2-positive breast cancer cells and regulates epithelial-mesenchymal transition - Sunmian Xu; Xiaohui Li; Wenbin Li; Nina Ma; Hongjun Ma; Jian Cui; Xiaogang You; Xuexin Chen (Clinical & Experimental Metastasis, 2023)

Response of soil carbon fractions and enzyme activities to mowing management on in a coastal wetland of the yellow river delta - Qian Cui; Hongjun Yang; Guangmei Wang; Jinzhao Ma; Lu Feng; Jingtao Liu (Frontiers in Marine Science, 2022)
Coastal wetlands are considered as important “blue carbon” sink, and mowing management induced by anthropogenic activities is anticipated to profoundly affect soil carbon stocks in coastal wetlands. However, the impacts of mowing management on soil organic carbon (SOC) and enzyme activities and the mechanisms responsible for associated changes in Phragmites australis wetland remain uncertain. We conducted a field mowing manipulation experiment [control (CK), mowing and returning straw in December (12MS), mowing and removing straw in December (12MR), mowing and returning straw in March (3MS), and mowing and removing straw in March (3MR)] in P. australis wetland of the Yellow River Delta and quantified their impacts on soil quality, SOC, SOC fractions, and enzyme activities. Results showed that mowing treatments led to overall increases in soil nutrients [total carbon (TC), total nitrogen (TN), total phosphorus (TP), NH 4 + , and NO 3 − ] and decreases in soil C/N ratio. The effects of mowing treatments on soil nutrient content were pronounced on topsoil than deep soil, and the maximum value of TC, TN, and TP reached in the 12MR treatment. Compared with CK, the 12MS, 12MR, 3MS, and 3MR treatments at 0–10 cm depth significantly enhanced SOC content by 8.78%, 32.9%, 16.5%, and 30.1%, respectively, but only the 3MS treatment enhanced SOC by 16.5% at 10–20 cm depth. Mowing treatments increased dissolved organic carbon (DOC), microbial biomass carbon (MBC), particulate organic carbon (POC), and labile organic carbon (LOC) and the contents of DOC, MBC, POC, and LOC decreased with soil depth. Mowing treatments stimulated the activities of sucrase and urease in topsoil, but only the 3MR treatment improved alkaline phosphatase activity in topsoil. Path analysis indicated that mowing management dominantly modulates SOC by changing sucrase activity, alkaline phosphatase activity, TN, TP, NH 4 + , NO 3 − , DOC, and LOC in 0–10 cm depth. However, SOC was significantly controlled by sucrase activity, urease activity, TC, TN, TP, LOC, and POC in 10–20 cm depth. Collectively, our results indicate that the continuous mowing management is beneficial to enhance soil quality and carbon storage capacity of P. australis wetlands, which will contribute to enhance carbon sequestration and sink capacity of coastal wetlands.

Productivity calculating method in tight gas reservoirs considering the stress sensitivity - Jie He; Xiangdong Guo; Hongjun Cui; Kaiyu Lei; Yanyun Lei; Lin Zhou; Qinghai Liu; Yushuang Zhu; Linyu Liu (Arabian Journal of Geosciences, 2022)

Magnetic properties indicate the sources of hadal sediments in the Yap Trench, northwest Pacific Ocean - Yu Chen; Jichao Yang; Olusegun A. Dada; Yaomin Yang; Zhen Lin; Zhen Cui; Yue Xu; Hongjun Yu; Baohua Liu (Journal of Oceanology and Limnology, 2020)

Pm61: a recessive gene for resistance to powdery mildew in wheat landrace Xuxusanyuehuang identified by comparative genomics analysis - Huigai Sun; Jinghuang Hu; Wei Song; Dan Qiu; Lei Cui; Peipei Wu; Hongjun Zhang; Hongwei Liu; Li Yang; Yunfeng Qu; Yahui Li; Teng Li; et al. (Theoretical and Applied Genetics, 2018)

Altered cerebro-cerebellum resting-state functional connectivity in HIV-infected male patients - Huijuan Wang; Ruili Li; Yawen Zhou; Yanming Wang; Jin Cui; Benedictor Alexander Nguchu; Bensheng Qiu; Xiaoxiao Wang; Hongjun Li (Journal of NeuroVirology, 2018)